1997
DOI: 10.1136/bmj.315.7120.1426
|View full text |Cite
|
Sign up to set email alerts
|

The validity of general practitioners' self assessment of knowledge: cross sectional study

Abstract: Objective: To determine whether general practitioners can make accurate self assessments of their knowledge in specific areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 8 publications
3
76
1
6
Order By: Relevance
“…So far, several tools for physicians' self-assessment have been used (1). Some of them measured basic medical knowledge (15,16), some basic clinical skills (17,18) and some specific clinical knowledge and skills (19,20). None of them was specifically based on the proposed competency framework such as some of the other tools were (21).…”
Section: Introductionmentioning
confidence: 99%
“…So far, several tools for physicians' self-assessment have been used (1). Some of them measured basic medical knowledge (15,16), some basic clinical skills (17,18) and some specific clinical knowledge and skills (19,20). None of them was specifically based on the proposed competency framework such as some of the other tools were (21).…”
Section: Introductionmentioning
confidence: 99%
“…McKenna, Stanier, & Lewis, 1991) showed that people generally believe that their driving is above average; this applies to overall competence, as well as to individual manoeuvres such as overtaking. Similarly, studies conducted on general practitioners showed weak correlations between self-assessed medical knowledge and objective knowledge (Tracey, Arroll, Richmond, & Barham, 1997). At last, various examples demonstrated that people do not always stay silent when they do not know something.…”
mentioning
confidence: 99%
“…The positive relationship between patient mix and selfassessment outcome (compared with formal assessment) is not per se an indication of a relationship between patient mix and learning. Self-assessments have many limitations, as is discussed in several reviews, all concluding that self-assessment has little validity and reliability (Tracey et al 1997; Eva &…”
Section: Discussionmentioning
confidence: 99%